2016
DOI: 10.16986/huje.2016023171
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Organizational Ethical Climate and Political Behavior Perceptions of the Faculty Members

Abstract: ABSTRACT:The purpose of this study is to investigate the relationships between organizational ethical climate and political behavior on the basis of the faculty members' perceptions. The sample of the study is comprised of 440 faculty members employed at Mugla Sıtkı Kocman University. The data of the study were collected through the Ethical Climate Questionnaire and the Political Behavior Questionnaire. In the analysis of the data, descriptive statistics, t-test, ANOVA, LSD test, and multiple regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
4
0
2
Order By: Relevance
“…In the study of Shafipour et al (2016), ethical climate perception did not show a statistical difference by gender. Similarly, in the study conducted by Ekinci (2017), faculty members' perceptions of ethical climate do not differ significantly according to gender and academic title. When the findings of the research were examined in general, the ethical climate perception of the female participants was more positive than the male participants.…”
Section: Discussionmentioning
confidence: 76%
“…In the study of Shafipour et al (2016), ethical climate perception did not show a statistical difference by gender. Similarly, in the study conducted by Ekinci (2017), faculty members' perceptions of ethical climate do not differ significantly according to gender and academic title. When the findings of the research were examined in general, the ethical climate perception of the female participants was more positive than the male participants.…”
Section: Discussionmentioning
confidence: 76%
“…In separate studies, it was found that when employees" perceptions of organizational ethical climate were low, the theft in the workplace and organizational unethical behaviors were higher [88], [86]. It has been demonstrated that caring, law and code, and rules dimensions has positive impacts on positive outcomes, whereas instrumental and independence climates have positive impacts on negative outcomes in the organizations [89], [90], [91], [92], [93], [94]. In particular, significant correlations between the dimensions of EC and employee deviance and counterproductive work behaviors have been revealed in previous studies [55], [54], [87], [95].…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…In the literature, studies of the same topic have reported different results. It was found that academics working in different fields in Turkey perceived the ethical climate in their institutions at a moderate level (Ekinci 2017). They also perceived the most favourable ethical climate in laws and professional codes, and the most negative ethical climate was in efficiency and benevolence (Ekinci 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that academics working in different fields in Turkey perceived the ethical climate in their institutions at a moderate level (Ekinci 2017). They also perceived the most favourable ethical climate in laws and professional codes, and the most negative ethical climate was in efficiency and benevolence (Ekinci 2017). A study conducted in various faculties of a university in Croatia found that laws and professional codes was dominant in general, that a climate of self‐interest was more dominant in the medical faculty and that friendship was the most negatively perceived type of ethical climate (Malicˇki et al 2019).…”
Section: Discussionmentioning
confidence: 99%